CRÓNICA DE UNA MOVILIZACIÓN ANUNCIADA: TODOSSOMOSAYOTZINAPA - Fernández Poncela, Anna María (2018)
This text focuses on analysing the achievements of Ayotzinapa movement from the social point of view. After the facts in Iguala town in Guerrero State in the year 2014, where 6 people were killed and 43 students disappeared, a movement arose in Mexico. Since the academy is usually study the origins and causes of the movements, but in this case intends to analyze achievements and their consequences. To do this, interviews were conducted with participants and a survey of the citizenship, in addition to the general literature review, and the self-reflection. As conclusion, it was a movement that moved and touched wide sectors of the population, being valued positively.